2018
DOI: 10.1021/acscatal.8b01999
|View full text |Cite
|
Sign up to set email alerts
|

Tailored NiOx/Ni Cocatalysts on Silicon for Highly Efficient Water Splitting Photoanodes via Pulsed Electrodeposition

Abstract: Converting solar energy by photoelectrochemical water splitting has been regarded as a promising way to resolve the global energy crisis and alleviate environmental pollution. Silicon, which is earth-abundant and has a narrow band gap, is an attractive material for photoelectrochemical water splitting. However, Si-based photoelectrodes suffer from photocorrosion, which leads to instability in electrolytes and high overpotential. Herein, we have fabricated a metal–insulator–semiconductor structure of NiO x /Ni/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 49 publications
0
83
0
Order By: Relevance
“…Many advanced bimetallic (hydro)oxide OER electrocatalysts based on Ni(OH) 2 and Co 3 O 4 have been explored via electrodeposition. [32][33][34][35] In this minireview, we focus on the recent discoveries of electrode preparation and OER applications of (hydro)oxides using the electrodeposition technique.…”
Section: Metal (Hydro)oxide Structures and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many advanced bimetallic (hydro)oxide OER electrocatalysts based on Ni(OH) 2 and Co 3 O 4 have been explored via electrodeposition. [32][33][34][35] In this minireview, we focus on the recent discoveries of electrode preparation and OER applications of (hydro)oxides using the electrodeposition technique.…”
Section: Metal (Hydro)oxide Structures and Propertiesmentioning
confidence: 99%
“…In principle, a synthetic method capable of producing ne grains can be used to produce nanomaterials. In the past few years, a number of important advances have been made in the electrodeposition of metal oxide nanoparticles such as NiO, 33 43,78 Electrodeposition involves the deposition of ions on to an electrode surface in an electrolyte via electrochemical reactions using direct current or pulsed electric elds. In order to obtain nanomaterials, the nucleation rate needs to be increased and the growth rate decreased.…”
Section: Morphology Design Of Metal (Hydro)oxidesmentioning
confidence: 99%
“…Copyright 2015, The American Chemical Society. f) The potential‐time curve of pulsed electrodeposition of Ni . g) The PEC performance of different Ni‐modified n‐Si photoanodes.…”
Section: Strategies For Semiconductor/electrocatalyst Couplingmentioning
confidence: 99%
“…Recent reports by our group, and others, have demonstrated that aqueous electrodeposition of transition metals nanoparticles (NPs) on n‐Si is effective to prepare inhomogeneous Si/metal Schottky junctions that can be further employed as stable Si‐based photoanodes without protection layer. This type of photoanode has been reported, so far, for n‐Si/Ni and n‐Si/Co junctions and it has been recently shown that the performance of these systems can be enhanced by using an additional catalytic shell, typically a hydroxide, or a metallic coating, over the NPs. To the best of our knowledge, this phenomenon has never been applied to n‐Si/Fe junctions so far, which we present for the first time in this article.…”
Section: Introductionmentioning
confidence: 99%